On the applicability of composite PA6-TiO2 filaments for the rapid prototyping of innovative materials and structures. (15th June 2018) - Singh, Rupinder; Kumar, Ranvijay; Mascolo, Ida; Modano, Mariano
Abstract: In the present paper a meticulous study for controlling the process parameters of twin screw extruder has been highlighted for in-house preparation of reinforced PA6-TiO2 hybrid feed stock filament (HFSF) of fused deposition modelling (FDM) for applications in several engineering fields. The experimental study has been reported for field engineers, to understand the influence of twin screw extrusion (TSE) process parameters on mechanical and metallurgical properties of Nylon-TiO2 HFSF for printing of functional prototypes by FDM, with special focus on the additive manufacturing of innovative composite materials and structures with arbitrary geometry at different scales. These properties were statistically compared to verify the suitability of the screw extrusion process. The study suggested the long-term performance level of the TSE process after it has been brought under statistical control. The provided data from the experimentation highlights the ability of the TSE process to produce a product that will consistently meet the design requirements and the customer expectation. Highlights: The process parameters of PA6-TiO2 composite filaments for FDM are characterized. The best settings are: barrel temperature 2500 C, extruder RPM 50 and load 15 kg. PA6-TiO2 filaments are suited for the FDM of innovative materials and structures.